Use of Extralinguistic Knowledge in Translation - Kim, Ryonhee (Meta)

(untitled) (Les Presses de l'Université de Montréal, 2006)
AbstractA competent translator seems to make extensive use of inferential strategies in the process of understanding a source text in translation. It also appears that extralinguistic knowledge plays an important role in this inference. However, it has not been determined how important it is relative to other components of translator competence and in what way it is important. This study investigated the use of extralinguistic knowledge in comprehension processes by analyzing data from L2->L1 translation, a questionnaire and a think-aloud study. Professional translators, translation students (or semi-professionals), and language learners participated in the study. Major (albeit tentative) findings are the following: (i) The use of extralinguistic knowledge that is most relevant for a specific translation problem makes the inferential process more concise and efficient and it leads to a higher-quality translation; (ii) “Translation effort” can compensate for overall lack of linguistic and extralinguistic competence in translation. It is suggested that a translator needs to have a broad base of specialized knowledge as well as world knowledge. Also, s/he should bear in mind that the greater the effort or involvement with the translation, the better the output.